PENGARUH STRES KERJA DAN KOMPENSASI TERHADAP KOMITMEN INDIVIDU DAN KINERJA KARYAWAN PT. INDOFOOD SUKSES MAKMUR TBK DIVISI BOGASARI KALIMANTAN SELATAN - M. Ridhoni Arifin; I Dewa Ketut Raka Ardiana; Murgianto Murgianto (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2019)
Employee’s job performance is a fundamental thing that supports the company in achieving its goals. Then an evaluation is carried out so that the company can know the performance of its employees so that research is carried out. The objectives of this study are: (1). Effect of work stress on individual commitment to employees of PT Indofood Sukses Makmur Tbk Bogasari Division. (2). Effect of work stress on the performance of employees of PT Indofood Sukses Makmur Tbk Bogasari Division. (3). Effect of compensation on individual commitments on employees of PT Indofood Sukses Makmur Tbk Bogasari Division. (4). Effect of Compensation on the performance of employees of PT Indofood Sukses Makmur Tbk Bogasari Division. (5). Influence individual commitment to the performance of employees of PT Indofood Sukses Makmur Tbk Bogasari Division. The population in this study were 192 people, the method used in this study was the survey method. The analysis technique used in this study is SEM (Structural Equation Modeling). The results of this analysis indicate that: H1. Work structure has a significant effect on individual commitment to employees of PT Indofood Sukses Makmur Tbk Bogasari Division. South Kalimantan. H2.Stres work has a significant effect on the performance of employees of PT Indofood Sukses Makmur Tbk, Bogasari Division, South Kalimantan. H3. Compensation has a significant effect on individual commitment to employees of PT Indofood Sukses Makmur Tbk Bogasari Division. South Kalimantan. H4. Compensation has a significant effect on the performance of PT Indofood Sukses Makmur Tbk Bogasari Division employees. South Kalimantan. H5. Individual commitment significantly influences the performance of employees of PT Indofood Sukses Makmur Tbk Bogasari Division. South Kalimantan.Keywords: Job Stress, Compensation, Individual Commitment, Employee Performance.